FRI0443 Digital artery volume index: the first objective, automated, non-invasive imaging diagnostic of macrovascular involvement in ssc. (12th June 2018) - Lettieri, G.; Abignano, G.; Bagnato, G.; Eng, S.; Ridgeway, J.P.; Kaftan, J.N.; Hinton, M.; Kubassova, O.; Buch, M.H.; Emery, P.; O'Connor, P.; Del Galdo, F.
Abstract : Background: Macrovascular involvement in Systemic Sclerosis (SSc) is caused by proliferation of vascular smooth muscle cells within the intima of arteries (neointimal proliferation). The resulting decrease in arterial volume is responsible for the severity of Raynaud's and for the onset of severe clinical manifestations such as Renal Crisis and Pulmonary Artery Hypertension. Several RCTs have demonstrated the efficacy of Endothelin Receptor Antagonists (ERAs) in targeting neointimal proliferation, which makes them to date, the only disease modifying agent available in SSc. Nevertheless, the lack of validated early diagnostics means the intention to treat with ERAs remains limited to the diagnosis of end stage clinical manifestations of neointimal proliferation, such as presence of Digital Ulcer (DU) and PAH. Objectives: Here we aimed to determine the proof of concept validity of automated Digital Artery Volume Index (DAVIX) measured by non-contrast Time of Flight (TOF) MRI as an objective diagnostic tool to be used as surrogate outcome measure of neointimal proliferation in SSc. Methods: 10 Healthy Volunteers (HV) and 8 SSc patients were enrolled. Six patients underwent longitudinal assessments at least 12 months apart. MRI scans were performed on a 3T Magnetom Verio (Siemens) and consisted of a VIBE 3D T1 scan and a 2D TOF sequence of 8 min. DAVIX was calculated as the percentage of the ratio of digital artery and the respective finger volumes. The vessels and fingers were manually outlined by an expert radiologist and used as a 'gold standard' (DAVIX-1) and compared to a 2nd independent radiologist assessment (DAVIX-2). An automated segmentation algorithm was developed using threshold based segmentation and region growing (DAVIX-A) and validated against gold standard. Intraclass correlation coefficient (ICC) and absolute agreement were calculated to estimate reliability. Bland-Altman bias and 95% limits of agreement (LoA) were calculated as well. Results: SSc patients and HV had comparable age (44±8 vs 45±8) and gender (F:M=5:2 vs 4:2). 4 fingers were affected by DUs at baseline and two fingers were affected by new DU at follow up. Mean(±SD) DAVIX in HV was 1.21 (±0.39) with no significant difference among individual fingers. Mean DAVIX in SSc patients was 0.37 (±0.18) and 0.32 (±0.39) at baseline and follow-up, respectively (p<0.0001 vs HV for both). The fingers with DU had an average DAVIX of 0.24 (±0.08) vs 0.40 (±0.18) of the fingers without DU (p=0.02). DAVIX changed over time in both directions. In the fingers affected by new DU, DAVIX dropped by 56% (0.161 vs 0.072) and 86% (1.149 vs 0.132), respectively. ICC among two independent readings was 0.90 (95% LoA −0.139, 0.118) with overall r 2 =0.74 (p<0.0001). Automated segmentation showed superior correlation to gold standard with r 2 =0.80 (p<0.0001). Conclusions: This proof of concept study demonstrated validity and sensitivity to change of DAVIX for the automated volumetric assessment of digital arteries, which reflected clinical worsening in patients with new DU. Larger, longitudinal studies are planned to assess DAVIX' predictive value for the onset of DU and its potential use as early diagnostic of neointimal proliferation in SSc. Disclosure of Interest: None declared